Do sonho ao pesadelo : impactos na saúde mental de mulheres/mães que tiveram filhos durante a pandemia da Covid-19 - Silva, Francisca Vilena da (2024)
Introduction: The COVID-19 pandemic contributed significantly to the increase in factors that may have impacted the mental health of women/mothers, such as work overload, the accumulation of domestic tasks and the multiple responsibilities performed at home, leading to to physical and emotional exhaustion. Objectives: To analyze the impacts of the COVID-19 pandemic on the mental health of women/mothers who had children during the pandemic; Explore the feelings/emotions most experienced at this time by women/mothers who had children during the pandemic; Understand how gender inequality has influenced the mental health of women/mothers who have had children during the COVID-19 pandemic. Method: This is an exploratory, descriptive research with a qualitative approach, using Bola de Neve sampling, with 10 women/mothers who had children during the pandemic. The interviews were guided by a semi-structured script via Google Meet. The data was organized and analyzed using Bardin's Thematic Modality Content Analysis Technique. The research project was approved by the CEP of the UFPB Health Sciences Center, under opinion nº 6.330.015 and CAAE nº 74083923.4.0000.5188. Results: The study showed that women/mothers had to deal with a variety of feelings in their daily lives, including concerns about their health, fear of dying, of becoming infected and of contaminating their child at birth. Furthermore, women/mothers reported that they felt anxiety and anguish about the future during pregnancy and frustration with the uncertainties of the situation, in addition to overload and exhaustion. Final considerations: The pandemic negatively and disproportionately impacted women/mothers. It exposed and worsened gender inequalities, affecting women's health, rights and freedom.